Treatment of coronoid hyperplasia by coronoidotomy: An integrative literature review (Research, Society and Development, 2025)
Introduction: Hyperplasia of the coronoid process of the mandible is an uncommon condition of uncertain etiology, characterized by abnormal elongation of the process, with consequent limitation of mandibular movement. Coronoidotomy is a treatment technique that consists of osteotomy and burial of the hyperplastic fragment, and is considered less invasive and simpler than the more common technique, coronoidectomy. Objective: This study aims to analyze, through an integrative literature review, the results obtained in the treatment of coronoid process hyperplasia using the coronoidotomy technique. Methodology: A search was conducted in the PubMed/Medline, LILACS, Scopus, and Web of Science databases, including studies in all languages, with no restrictions on publication date. Based on the inclusion and exclusion criteria, 10 studies were selected for analysis. Conclusion: It was concluded that coronoidotomy is an effective technique for treating coronoid process hyperplasia, presenting satisfactory results in maintaining patients' mouth opening.